METHODS OF FINANCING AGRICULTURAL, SCIENTIFIC INSTITUTIONS AND INVESTMENT PROJECTS (American Journal of Research in Humanities and Social Sciences, 2024)
This article will consider the methods of financing scientific institutions and investment projects in the field of Agriculture.The study of the issues of modernization of agricultural production and scientific institutions, technical and technological re-equipment, financing of investment projects, the most important sphere of the country's economy, is a priority of today. The article is devoted to the problems of expanding the scope of research work in agriculture, introducing scientific results into practice, increasing investment activity. The agricultural sector consists of a reasonable conclusion, scientific proposal and practical recommendations on the use of budgetary, non-governmental sources of research funding, the use of farms and farms, as well as other methods.